Лингвокультурологические аспекты невербальной коммуникации - Orzechowska, Joanna (Studia Rossica Posnaniensia, 2021)
The article presents the issue of non-verbal communication from the perspective of translation and teaching a foreign language. The research is based on an experiment conducted among Russian students at the University of Warmia and Mazury, whose task it was to analyze data from Krystyna Jarząbek’s Dictionary of the Body Language of Polish People, from which about 30 unknown or unintelligible units of non-verbal communication were selected. The data show that body language, including gestures, is culture-rooted, and confirm that non-verbal means play a significant role in communication. This is why the author of the article believes it to be justified to introduce elements of non-verbal communication into teaching foreign languages and to compile bilingual dictionaries of body language.